Efektivitas Layanan Pajak Pada Kantor Pelayanan Penyuluhan Dan Konsultasi Perpajakan Benteng Kabupaten Kepulauan Selayar - Farida, Yusni; Madani, Muhlis; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
Thisbstudy aimed to find out the effectiveness of tax services at the tax counseling and counseling service office for the Selayar Islands Regency. This study used a qualitative method. Data collection techniques were observation, interviews, and documentation. The informants in the study consisted of 6 (six) people. The results of this study showed that 1) Achievement of goals. whereKP2KP Benteng provided good service in accordance with the SOP issued by the directorate general of taxes. 2) Integration, socialization carried out by KP2KP Benteng in accordance with operational technical instructions and carried out quite well, in order to provide understanding to taxpayers regarding the rights and obligations of taxpayers, 3) Adaptation, facilities and infrastructure at KP2KP Benteng were adequate enough to assist the service process well, but the service was still often hampered by the usual network that was often disconnected due to the lights that often turn off but this could be handled properly.Keywords: Effectiveness, Tax, Service